Cobalt nanowire and its preparation method

By using cobalt nano interconnect wires and their preparation methods in integrated circuits, problems such as increase in barrier layer thickness and copper migration encountered by copper interconnect wires in the development of high density and low power consumption are solved, achieving efficient conductivity and improving chip reliability.

CN119581414BActive Publication Date: 2025-05-02LANZHOU UNIV

Patent Information

Application Number
CN202510122964.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-05-02
Estimated Expiration
2045-01-26

AI Technical Summary

Technical Problem

In the process of high-density and low-power consumption development of integrated circuits, the reduction in the characteristic size of copper interconnects leads to an increase in the thickness of the barrier layer, a decrease in the effective conductive area, and an increase in the resistance, which also triggers copper migration and parasitic effects. It is difficult for existing barrier layer materials and preparation processes to effectively deal with these challenges.

Method used

Cobalt nano interconnection lines and their preparation methods are adopted to obtain cobalt nano interconnection lines by magnetron sputtering on one side of the dual-pass PC film, electrodepositing the Cu layer and cobalt nano interconnection lines, peeling off the Au layer and dissolving the dual-pass PC film. This method combines magnetron sputtering and electrodeposition technology to achieve controlled growth and high purity preparation of cobalt nano interconnects.

Benefits of technology

Through the preparation of cobalt nano interconnects, the impact of the barrier layer on the conductive area can be effectively reduced, the resistance is reduced, the copper migration and parasitic effects can be reduced, the reliability of the interconnects and the service life of the chip can be improved, while simplifying the manufacturing process and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581414B_ABST
    Figure CN119581414B_ABST
Patent Text Reader

Abstract

The present application provides a cobalt nano-interconnect and a preparation method thereof, which belongs to the field of integrated circuits. The present application deposits an Au layer on one side of a double-pass PC film by magnetron sputtering, electro-deposits a Cu layer on the Au layer, electro-deposits a cobalt nano-interconnect in the pores of the double-pass PC film, peels off the Au layer from the double-pass PC film, dissolves the double-pass PC film and centrifuges to obtain the cobalt nano-interconnect. The present application combines magnetron sputtering and electro-deposition technology to achieve controllable growth of cobalt nano-interconnects, which has high compatibility with current chip interconnection processes; by controlling the electro-deposition process parameters, the texture and aspect ratio of the cobalt nano-interconnect can be regulated. The method has simple steps, is easy to realize industrial production, reduces production costs, and the prepared cobalt nano-interconnect has broad application potential in the fields of chip interconnection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of integrated circuits, and in particular to a cobalt nano interconnection wire and a preparation method thereof. Background Art

[0002] With the rapid development of large-scale integrated circuit technology towards high density and low power consumption, the feature size of integrated circuits has been sharply reduced. For copper interconnects, when the line width is reduced to 10 nm and sub-10 nm process technology, a significant problem is that the thickness of the barrier layer increases relatively, occupying more effective cross-sectional area of ​​the interconnect, resulting in a decrease in the effective conductive area of ​​copper and a sharp increase in resistance. At the same time, the reduction in process inevitably leads to serious copper migration and increased parasitic effects such as capacitance and inductance. In order to effectively cope with these severe challenges, studying new barrier layer materials and preparation processes and developing new interconnect materials are key strategies in the semiconductor manufacturing field to cope with the challenges of advanced processes. Ultra-thin liner / barrier materials with low resistivity, high diffusion barrier and weak surface scattering are used to minimize the influence of the barrier layer on the effective conductive area of ​​the interconnect while effectively blocking copper diffusion. However, since the mean free path of copper is 40 nm, the role that ultra-thin barrier materials can play in improving the interconnect performance of copper is extremely limited, and the preparation process of new barrier materials is usually more complicated, and there are still problems with compatibility with existing chip production processes. Compared with improving the performance of existing copper interconnects, developing new interconnect materials has greater potential.

[0003] In view of this, it is necessary to develop a cobalt nanointerconnect and a preparation method thereof to solve the above problems. Summary of the invention

[0004] In view of the technical problems existing in the background technology, the present application provides a cobalt nanointerconnect wire and a preparation method thereof, aiming to provide a technical reference and process basis for the application of cobalt nanointerconnect wire in high-performance chips.

[0005] In a first aspect, the present application provides a method for preparing a cobalt nanowire, comprising the following steps:

[0006] S1. Depositing an Au layer on one side of the double-pass PC film by magnetron sputtering;

[0007] S2. electrodepositing a Cu layer on the Au layer;

[0008] The method for electrodepositing the Cu layer is as follows: injecting a Cu electrodeposition solution into one side of an electrodeposition tank, using a Cu rod as an anode, a saturated calomel electrode as a reference electrode, and the Au layer obtained in step S1 as a deposition cathode to electrodeposit the Cu layer;

[0009] S3. Electrodeposit cobalt nanowires in the pores of the double-pass PC membrane, and connect the cobalt nanowires to the Au layer;

[0010] The method for electrodepositing cobalt nanowires is as follows: Inject the cobalt electrodeposition solution into one side of the electrodeposition cell, adjust the pH value of the cobalt electrodeposition solution to a predetermined range, use a cobalt rod as the anode, a saturated calomel electrode as the reference electrode, and the Au layer obtained in step S1 as the deposition cathode to electrodeposit cobalt nanowires;

[0011] The pH value of the cobalt electrodeposition solution is 2 - 5.5;

[0012] When pH = 2, the texture of the cobalt nanowires is

[110] ;

[0013] When 2 < pH < 3.5, the texture of the cobalt nanowires is

[100] and

[110] ;

[0014] When 3.5 ≤ pH ≤ 5.5, the texture of the cobalt nanowires is

[100] ;

[0015] S4. Peel the Au layer from the double-pass PC membrane to separate the cobalt nanowires from the Au layer;

[0016] S5. Place the double-pass PC membrane after peeling off the Au layer in an organic solvent for dissolution, and then perform centrifugal separation to obtain cobalt nanowires.

[0017] As a further improvement of the present application, in step S1, the film thickness of the double-pass PC membrane is 6 - 30 μm, the pore diameter is 10 - 100 nm; the thickness of the Au layer is 250 - 350 nm; the vacuum degree of the magnetron sputtering is 9.0×10 -4 ~1.0×10 - 4 Pa, the sputtering power is 30 - 200 W, and the sputtering time is 5 - 30 min.

[0018] As a further improvement of the present application, in step S2, the Cu electrodeposition solution includes CuSO4 and H2SO4; the deposition voltage for electrodepositing the Cu layer is -1.5~-0.6 V, the deposition time is 800 - 2000 s, and the reduction charge is 10 - 30 C.

[0019] Furthermore, the molar ratio of CuSO4 to H2SO4 is 1:(0.1 - 0.2). The thickness of the Cu layer is 10 - 30 μm.

[0020] As a further improvement of the present application, in step S3, the cobalt electrodeposition solution includes CoSO4 and H3BO3; the deposition voltage of the electrodeposited cobalt nanointerconnect wires is -1.6~-1.0 V, and the deposition time is 1000~1500 s.

[0021] Furthermore, the molar ratio of CoSO4 and H3BO3 is 1:(0.1~0.5).

[0022] As a further improvement of the present application, in step S5, the organic solvent is dichloromethane, and the dissolution time is 1 to 2 h.

[0023] In a second aspect, the present application provides a cobalt nanointerconnect wire, which is prepared by the preparation method of the cobalt nanointerconnect wire described in the first aspect, and the aspect ratio of the cobalt nanointerconnect wire is (60~3000):1.

[0024] The beneficial effects of this application are:

[0025] The present application provides a cobalt nano-interconnect and a preparation method thereof, wherein an Au layer is deposited on one side of a double-pass PC film by magnetron sputtering, a Cu layer is then electrodeposited on the Au layer, a cobalt nano-interconnect is electrodeposited in the pores of the double-pass PC film, the Au layer is peeled off the double-pass PC film, the double-pass PC film is dissolved and centrifuged to obtain the cobalt nano-interconnect. The present application combines magnetron sputtering and electrodeposition technology to achieve controllable growth of cobalt nano-interconnects, prepare structurally stable cobalt nano-interconnects, and have high compatibility with current chip interconnection processes; by controlling electrodeposition conditions, the texture and aspect ratio of the cobalt nano-interconnect can be controlled to meet actual interconnection requirements. The method has simple steps, is easy to realize industrial production, and reduces production costs; the organic solvents and chemicals used in the preparation process are relatively environmentally friendly and easy to handle, reducing the impact on the environment; the prepared cobalt nano-interconnect has broad application potential in the fields of chip interconnection and the like.

[0026] Compared with copper, cobalt has relatively high cohesive energy and less obvious electromigration, which can effectively reduce problems such as metal atom migration and wire breakage caused by electromigration, and improve the reliability of interconnects and the service life of chips. In addition, when using cobalt as an interconnect material, a thinner barrier layer can be used or a barrier layer as strict as copper can be unnecessary, which reduces the impact of the barrier layer resistance on the overall interconnect resistance and simplifies the manufacturing process.

[0027] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 This is a flow chart for preparing cobalt nanointerconnects in an embodiment of the present application;

[0030] Figure 2 This is a scanning electron microscope image of the cobalt nanointerconnect provided in Examples 1-4 of the present application at a magnification of 10k;

[0031] Figure 3 This is a scanning electron microscope image of the cobalt nanointerconnect provided in Example 1 of the present application at a magnification of 3k;

[0032] Figure 4 The X-ray diffraction pattern of the cobalt nanointerconnect provided in Example 3 of the present application;

[0033] Figure 5 X-ray diffraction patterns of cobalt nanointerconnects provided in Examples 1 and 5-11 of the present application;

[0034] Figure 6 This is a graph showing the effect of pH on the texture coefficient of cobalt nano-interconnects in Example 1 and Examples 5-11 of the present application;

[0035] Figure 7 The interconnection structure model and electrical measurement schematic diagram of the cobalt nanointerconnection wire provided in Example 1 of the present application, and the top view of the interconnection structure;

[0036] Figure 8 This is a graph showing the electrical performance test of the cobalt nanowires provided in Example 1 of the present application;

[0037] Fig. 9 The model structures of different crystal planes of the cobalt nanointerconnect wire in the embodiment of the present application;

[0038] Fig.10 The curve diagram of the change of the conductivity of the cobalt nano-interconnect wires with different crystal orientations as a function of voltage in the embodiment of the present application;

[0039] Fig.11 This is a graph showing the electrical properties of cobalt nanoparticles with different crystal orientations in the embodiments of the present application;

[0040] Fig.12 Graph showing transmission probability of cobalt nano-interconnects with different crystal orientations in the embodiment of the present application. DETAILED DESCRIPTION

[0041] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0043] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0044] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0045] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0046] The electron mean free path of traditional metals such as copper exceeds the characteristic size of the interconnect, resulting in performance degradation at extremely small sizes, limiting the further miniaturization of the interconnect. In order to solve the technical problems that the performance of traditional metal interconnect materials degrades as the characteristic size decreases and the preparation of ultra-fine interconnects is difficult to achieve high precision and high reliability, the present application provides a cobalt nano interconnect and a preparation method thereof, wherein the size and crystal structure of the cobalt nano interconnect are controlled by optimizing the electrodeposition process, and a cobalt nano interconnect that can meet the process size of 10 nm and below is prepared.

[0047] Please refer to Figure 1 , in a first aspect, an embodiment of the present application provides a method for preparing cobalt nano-interconnects, including the following steps:

[0048] S1. Magnetron sputter deposit an Au layer on one side of a double-pass PC membrane;

[0049] S2. Electro-deposit a Cu layer on the Au layer;

[0050] The method for electro-depositing the Cu layer is: injecting a Cu electro-deposition solution into one side of an electro-deposition tank, using a Cu rod as the anode, a saturated calomel electrode as the reference electrode, and the Au layer obtained in step S1 as the deposition cathode to electro-deposit the Cu layer;

[0051] S3. Electro-deposit cobalt nano-interconnects in the pores of the double-pass PC membrane, and the cobalt nano-interconnects are connected to the Au layer;

[0052] The method for electro-depositing cobalt nano-interconnects is: injecting a cobalt electro-deposition solution into one side of an electro-deposition tank, adjusting the pH value of the cobalt electro-deposition solution to a predetermined range, using a cobalt rod as the anode, a saturated calomel electrode as the reference electrode, and the Au layer obtained in step S1 as the deposition cathode to electro-deposit cobalt nano-interconnects;

[0053] The pH value of the cobalt electro-deposition solution is 2 - 5.5;

[0054] When pH = 2, the texture of the cobalt nano-interconnects is

[110] ;

[0055] When 2 < pH < 3.5, the texture of the cobalt nano-interconnects is

[100] and

[110] ;

[0056] When 3.5 ≤ pH ≤ 5.5, the texture of the cobalt nano-interconnects is

[100] ;

[0057] S4. Peel the Au layer from the double-pass PC membrane to separate the cobalt nano-interconnects from the Au layer;

[0058] S5. Place the double-pass PC membrane after peeling the Au layer in an organic solvent for dissolution, and then perform centrifugal separation to obtain cobalt nano-interconnects.

[0059] In the technical solution of the embodiment of the present application, cobalt nano-interconnects can be prepared by magnetron sputtering and electrodeposition technology. By sputtering an Au layer on a double-pass PC film (ion track polycarbonate film) as a deposition electrode for the cobalt nano-interconnects; electro-depositing a Cu layer on the side of the Au layer away from the double-pass PC film as a support layer to increase the mechanical stability of the entire structure; the double-pass PC film is used as a template, having bidirectional permeable channels, and cobalt nano-interconnects are electro-deposited in its channels to guide the directional growth of the cobalt nano-interconnects, which helps to form a structurally stable nanowire interconnect structure; utilizing the difference in adhesion between the Au layer and the Cu layer, and between the Au layer and the double-pass PC film, the Au layer is peeled off from the double-pass PC film through the edge stress generated by the Cu layer, and the double-pass PC film after the Au layer is peeled off is placed in an organic solvent to dissolve, so that the cobalt nano-interconnects can be effectively separated from the template, and further purified by centrifugal separation, thereby improving the cleanliness of the cobalt nano-interconnects and obtaining cobalt nano-interconnects with high purity and high aspect ratio. This method has good repeatability, and the size, shape and length of the nanowires can be controlled by adjusting the parameters of electrodeposition and double-pass PC membrane to meet different application requirements.

[0060] Through electrochemical deposition, a uniform Cu layer can be formed on the Au layer. The adhesion between the Cu layer and the Au layer is greater than that between the Au layer and the PC film. Using a pure Cu rod as an anode helps to improve the purity of the deposited Cu layer and reduce the influence of impurities. The Cu rod as an anode will dissolve during the electrolysis process, releasing Cu 2+ , maintaining the concentration balance of the electrodeposition solution. The saturated calomel electrode is used as a reference electrode to control the potential during the electrodeposition process to ensure the stability and repeatability of the deposition process. The Au layer, as the cathode, provides a uniform and conductive surface, which is conducive to the uniform deposition of the Cu layer. After the deposition is completed, the Cu deposition solution is replaced with deionized water to prevent the occurrence of replacement reaction in the subsequent steps.

[0061] Cobalt nanointerconnects are electrodeposited on the inner surface of the Au layer by using the nanopore confinement effect. The pores of the double-pass PC membrane serve as a template to guide the directional growth of cobalt nanointerconnects and form nanostructures with specific shapes and sizes. Cobalt rods with a purity of 5~6N (99.999%~99.9999%) are preferably used as anodes to reduce impurities entering the deposition layer and ensure the purity of the cobalt nanointerconnects. Cobalt nanointerconnects grow directly on the Au layer to ensure good electrical contact with the Au layer. After applying an appropriate current, cobalt ions are reduced to cobalt atoms by electrons on the cathode (Au layer), and cobalt nanointerconnects are gradually formed in the pores of the double-pass PC membrane on the surface of the Au layer. After the deposition is completed, the residual deposition liquid in the deposition tank is rinsed off to clean the sample surface.

[0062] The pH value of the cobalt electrodeposition solution is 2~5.5. The appropriate pH value can regulate the main texture of cobalt nanointerconnects. When the pH is lower than 2.0, the rate of hydrogen evolution reaction increases, and the generated hydrogen microbubbles hinder the diffusion of ions in the solution, making it impossible to obtain uniformly deposited cobalt nanointerconnects. When the pH is greater than 5.5, flocculent precipitates of cobalt hydroxide will appear in the CoSO4 deposition solution, resulting in a decrease in the concentration of cobalt ions.

[0063] Furthermore, in some embodiments, in step S1, the thickness of the double-pass PC film is 6-30 μm, the pore size is 10-100 nm; the thickness of the Au layer is 250-350 nm; the vacuum degree of magnetron sputtering is 9.0×10 -4 ~1.0×10 -4 Pa, the sputtering power is 30~200 W, and the sputtering time is 5~30 min.

[0064] In the technical solution of the embodiment of the present application, the film thickness and pore size of the double-pass PC film affect the growth length and diameter of the nano-interconnection line, and the appropriate film thickness and pore size can ensure the uniform growth of the nano-interconnection line. The thickness of the Au layer is within a certain range, which can ensure that the Au layer is more evenly deposited on the PC film while ensuring good electrical conductivity and adhesion. Under a lower sputtering vacuum, oxidation of the metal can be prevented, thereby obtaining a more uniform Au film with fewer defects. The sputtering time is controlled within the range of 5 to 30 minutes, which can ensure that the thickness of the Au layer is moderately uniform and continuous, and the Au layer will not be difficult to peel off after electrodeposition due to the Au layer being too thin, nor will the PC film be strained and curled due to the Au layer being too thick. The appropriate sputtering time helps to improve the uniformity and continuity of the Au layer on the surface of the PC film and reduce the problem of uneven thickness.

[0065] Further, in some embodiments, in step S2, the Cu electrodeposition solution includes CuSO4 and H2SO4; the deposition voltage of the electrodeposited Cu layer is -1.5~-0.6 V, the deposition time is 800~2000 s, and the reduction charge is 10~30 C.

[0066] In the technical solution of the embodiment of the present application, the deposition voltage is -1.5~-0.6 V (vs SEC, standard hydrogen electrode). The appropriate deposition voltage can promote the reduction of Cu ions while avoiding side reactions such as hydrogen evolution caused by excessively high voltage. The deposition time of 800~2000 s can ensure that the thickness of the Cu layer is moderate, neither too thin nor too thick. The reduction charge can control the thickness and deposition rate of the Cu layer and determine the amount of copper deposited on the cathode.

[0067] Further, in some embodiments, the molar ratio of CuSO4 to H2SO4 is 1:(0.1~0.2).

[0068] In the technical solution of the embodiment of the present application, the molar ratio of the electrodeposition solution can optimize the electrodeposition process, ensure the stable supply of Cu ions, and at the same time maintain the conductivity of the solution, which helps to form a uniform and dense Cu layer.

[0069] Furthermore, in some embodiments, the thickness of the Cu layer is 10-30 μm.

[0070] In the technical solution of the embodiment of the present application, the Cu layer of appropriate thickness can provide better mechanical strength and support, making the interconnection structure more stable. In addition, the Cu layer is used to facilitate the peeling of the Au layer in the subsequent processing process to obtain high-purity and high-dispersity cobalt nano-interconnect wires.

[0071] Furthermore, in some embodiments, in step S3, the cobalt electrodeposition solution includes CoSO4 and H3BO3; the deposition voltage of the electrodeposited cobalt nanointerconnect wires is -1.6~-1.0 V, and the deposition time is 1000~1500s.

[0072] In the technical solution of the embodiment of the present application, the deposition voltage of -1.6~-1.0 V (vs SEC, standard hydrogen electrode) can provide appropriate reduction power, promote the reduction of cobalt ions, and reduce the occurrence of side reactions. The deposition time of 1000~1500 s can make the cobalt nanointerconnects grow fully to the required length and structure. Too short a deposition time may result in insufficient growth, and the cobalt nanointerconnects do not have enough time to form a complete crystal structure, resulting in structural defects, and their mechanical strength and stability may not be sufficient to withstand the stress in subsequent processing or application. Too long a deposition time may cause the cobalt nanointerconnects to grow excessively or deteriorate in morphology, bifurcation, agglomeration or coarsening, affecting the physical and chemical properties of the cobalt nanointerconnects.

[0073] Further, in some embodiments, the molar ratio of CoSO4 to H3BO3 is 1:(0.1~0.5).

[0074] In the technical solution of the embodiment of the present application, the molar ratio of CoSO4 and H3BO3 can ensure the stability and deposition efficiency of the electrodeposition solution, and help form uniform and dense cobalt nano-interconnects.

[0075] Furthermore, in some embodiments, the organic solvent is dichloromethane, and the dissolution time is 1 to 2 h.

[0076] In the technical solution of the embodiment of the present application, dichloromethane has good solubility for PC film and little effect on the electrodeposited cobalt nanointerconnects, so the PC film can be removed without damaging the cobalt nanointerconnects. The shorter dissolution time can reduce the potential damage to the cobalt nanointerconnects and maintain their structure and performance. The cobalt nanointerconnects are collected, dispersed in an ethanol solution, and stored at low temperature to prevent oxidation.

[0077] In a second aspect, an embodiment of the present application provides a cobalt nanointerconnect wire, which is prepared by the preparation method of the cobalt nanointerconnect wire of the first aspect, and the aspect ratio of the cobalt nanointerconnect wire is (60~3000):1.

[0078] The aspect ratio of the cobalt nanowires prepared by the above method is (60~3000): 1, which ensures that the cobalt nanowires have sufficient length to meet the application requirements of the interconnects in integrated circuits while maintaining good mechanical properties. The aspect ratio is a key parameter for measuring the shape of nanowires. A higher aspect ratio means that the nanowires have better extensibility in the length direction, which is conducive to forming a continuous interconnect structure.

[0079] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0080] Example 1

[0081] Example 1 provides a method for preparing cobalt nanowires, such as Figure 1 As shown, the following steps are included:

[0082] S1. Magnetron sputtering Au electrode layer: A double-pass PC film with a pore size of 10 nm and a film thickness of 30 μm was placed in a magnetron sputtering instrument, and a layer of Au with a thickness of 300 nm was sputtered as the deposition electrode of the cobalt nanointerconnection line. The sputtering vacuum degree was 7.4×10 - 4 Pa, sputtering time 10 min.

[0083] S2. Electrodeposition of Cu layer: A 20 μm thick copper layer was electrodeposited on the PC film side of the Au layer. 1M CuSO4 and 0.1M H2SO4 electrodeposition solution were injected into one side of the double-hole electrodeposition tank. A 6N Cu rod was used as the anode, a saturated calomel electrode was used as the reference electrode, and the Au film was used as the deposition cathode. A voltage of -0.8 V (vs SEC) was applied for 1000 s of deposition, and the reduction charge was 20 C. After the Cu film deposition was completed, the Cu deposition solution was replaced with deionized water to prevent the occurrence of a replacement reaction during the deposition of the cobalt nanointerconnect wires.

[0084] S3. Electrodeposition of cobalt nanointerconnects: 1M CoSO4 and 0.4M H3BO3 were injected into one side of the three-hole deposition tank, the pH value of the electrodeposition solution was adjusted to 2, a 6N high-purity cobalt rod was used as the anode, a saturated calomel electrode was used as the reference, a voltage of -1.2 V (vs SEC) was applied, and constant voltage deposition was performed for 1200 s. After the deposition was completed, the residual deposition solution was rinsed. The double-pass PC membrane has nanopores. Using the confinement effect of the nanopores, cobalt ions diffuse along the nanopores and are reduced to cobalt elemental substance by electrons on the surface of the Au layer.

[0085] S4. Peeling off the Au layer: To facilitate the characterization and analysis of the cobalt nanointerconnects, the intrinsic properties of the cobalt nanointerconnects were analyzed to avoid interference from the Au layer. The difference in adhesion between the Au layer and the Cu layer, and between the Au layer and the PC was utilized. The edge stress generated by the Cu layer was used to peel off the Au layer from one side of the PC film, thereby disconnecting the cobalt nanointerconnects from the Au layer.

[0086] S5. Dissolving PC film: Taking advantage of the dissolution characteristics of PC film, the double-pass PC film after stripping the Au layer was immersed in 20 mL of dichloromethane solution and allowed to stand for 1 h. The double-pass PC film was depolymerized and dissolved to release cobalt nanowires. Monodispersed cobalt nanowires with a diameter of 10 nm were obtained by centrifugal separation. Finally, the cobalt nanowires were dispersed in an ethanol solution and stored at low temperature to prevent oxidation.

[0087] Example 2

[0088] Example 2 provides a method for preparing cobalt nanointerconnects. Compared with Example 1, the only difference is that the pore size of the double-pass PC membrane is 30 nm. The remaining experimental parameters and conditions are basically the same as those in Example 1 and are not repeated here. A cobalt nanointerconnect with a diameter of 30 nm is obtained.

[0089] Example 3

[0090] Example 3 provides a method for preparing cobalt nanointerconnects. Compared with Example 1, the only difference is that the pore size of the double-pass PC membrane is 50 nm. The remaining experimental parameters and conditions are basically the same as those in Example 1 and are not repeated here. A cobalt nanointerconnect with a diameter of 50 nm is obtained.

[0091] Example 4

[0092] Example 4 provides a method for preparing cobalt nanointerconnect wires. Compared with Example 1, the only difference is that the pore size of the double-pass PC membrane is 80 nm. The remaining experimental parameters and conditions are basically the same as those in Example 1 and are not repeated here. A cobalt nanointerconnect wire with a diameter of 80 nm is obtained.

[0093] like Figure 2 As shown, it is a scanning electron microscope image of the cobalt nanointerconnect wires provided in Examples 1-4 at a magnification of 10k, and ad represents cobalt nanointerconnect wires with diameters of 10 nm, 30 nm, 50 nm, and 80 nm, respectively. It can be seen that after the PC film is dissolved, the nanowires are evenly dispersed on the silicon substrate and the surface of the nanowires is relatively smooth.

[0094] Figure 3 The scanning electron microscope at 3k magnification of the cobalt nanointerconnect provided in Example 1 shows that the cobalt nanointerconnect with an aspect ratio of 3000:1 was successfully prepared by regulating the double-pass PC film and deposition parameters.

[0095] Figure 4 The X-ray diffraction pattern of the cobalt nanointerconnect provided in Example 3 shows that the diffraction peak position of the cobalt nanointerconnect with a diameter of 50 nm is consistent with the diffraction peak position of the JCPSD standard card (PDF# Co 05-0727), and the cobalt nanointerconnect corresponds to a hexagonal close-packed (HCP) structure. The diffraction peaks at 2θ of 41.6°, 44.59°, 47.44°, and 75.94° correspond to the diffraction peaks of the cobalt (100), (002), (101), and (110) crystal planes in the HCP structure, respectively, proving that the cobalt nanointerconnect with HCP structure was successfully synthesized by the electrodeposition method.

[0096] Example 5-11

[0097] Examples 5-11 respectively provide a method for preparing cobalt nanointerconnects. Compared with Example 1, the only difference is that the pH value of the cobalt electrodeposition solution is different, as shown in Table 1. The remaining experimental parameters and conditions are basically the same as those in Example 1 and will not be repeated here.

[0098]

[0099] Figure 5The XRD patterns of the cobalt nanointerconnects provided in Examples 1 and 5-11 show that 2θ values ​​of 41.68°, 44.76°, 47.56°, 75.94°, 90.62°, 92.54°, and 94.74° correspond to the (100), (002), (101), (110), (200), (112), and (201) crystal planes of the close-packed hexagonal cobalt structure, respectively. As the pH value increases from 2.5 to 5.5, the diffraction peak intensity of the (110) crystal plane gradually decreases. When the pH is 5.5, the diffraction peak of the (110) crystal plane disappears. The diffraction peak intensity of the (100) crystal plane shows a trend of first increasing and then decreasing with increasing pH. When the pH is 4.5, the diffraction peak intensity of the (100) crystal plane is the strongest. The results of XRD spectra show that the preferential growth of (110) and (110) crystal planes can be significantly regulated by adjusting the pH value, and under the deposition conditions, the crystal structure of cobalt nanointerconnects is an HCP structure.

[0100] Figure 6 The curves of the effect of pH value on the texture coefficient of cobalt nanointerconnects in Examples 1 and 5-11 show that the pH value has little effect on TC(002), TC(101), TC(112), and TC(201), but has a significant effect on TC(100) and TC(110). When the pH value increases from 2 to 3, the orientation of the prepared (110) crystal plane weakens, and the orientation of the (100) crystal plane strengthens. When the pH value is 2.5, both the (110) and (100) crystal planes show preferred orientation. At pH=2.0, TC(110)=5.01, and the main orientation in the cobalt nanointerconnect is the

[110] texture. When the pH value increases to 3.5, TC(100)=5.74, indicating that the favorable orientation of the cobalt nanointerconnect is mainly the

[100] texture. Therefore, the main texture of cobalt nanointerconnects can be regulated by adjusting the pH value of the cobalt deposition solution. When the pH value is 2, the texture of the cobalt nanointerconnect is

[110] . When the pH value is between 2-3.5 (excluding the end points), the texture of the cobalt nanointerconnect is

[100] and

[110] . When the pH value is 3.5-5.5, the texture of the cobalt nanointerconnect is

[100] . The texture of cobalt nanointerconnects affects their electrical transport properties. By regulating the main texture of cobalt nanointerconnects, the electronic transport properties of cobalt nanointerconnects can be improved, so that cobalt nanointerconnects can be applied in different fields.

[0101] Comparative Example 1

[0102] Comparative Example 1 provides a method for preparing cobalt nanointerconnects. Compared with Example 1, the only difference is that the pH value of the cobalt electrodeposition solution is 1, and the other experimental parameters and conditions are basically the same as those in Example 1, which will not be repeated here.

[0103] When the pH value is lower than 2.0, the rate of hydrogen evolution reaction increases, and the generated hydrogen microbubbles hinder the diffusion of ions in the solution, resulting in the inability to obtain a uniformly deposited cobalt nanointerconnect PC film.

[0104] Comparative Example 2

[0105] Comparative Example 2 provides a method for preparing cobalt nanointerconnects. Compared with Example 1, the only difference is that the pH value of the cobalt electrodeposition solution is 6. The other experimental parameters and conditions are basically the same as those in Example 1 and will not be repeated here.

[0106] When the pH value is 6, flocculent precipitates of cobalt hydroxide are generated in the CoSO4 deposition solution, the concentration of cobalt ions decreases, and the growth of cobalt nanointerconnects is uneven or broken, resulting in an incomplete structure of the cobalt nanointerconnects.

[0107] Figure 7 The interconnection structure model, electrical measurement schematic diagram, and interconnection structure top view of the cobalt nanointerconnect provided in Example 1 are as follows: Figure 7 The structure shown in the middle left figure is used to construct a vertical interconnection model. To facilitate measurement, the cobalt nanointerconnection wires are combined into a circular interconnection structure with a radius of 6 mm ( Figure 7 Five circular Au electrodes with a diameter of 2 mm are sputtered on top of the cobalt nanointerconnect (gray area in the middle right figure). Figure 7 Center right Figure 5 Yellow dots) were used to test the stability of cobalt nano-interconnects in different regions on an atmospheric probe station. Keithley 2636 B was used to measure IV characteristics, such as Figure 8 As shown, the contact area is 3.14 mm 2 The IV curve of the cobalt nanointerconnect below shows that the cobalt nanointerconnect has ohmic characteristics and is scanned 5 times repeatedly, showing good interconnection stability.

[0108] Fig. 9 This is the model structure of different crystal planes of the cobalt nanointerconnect wire in the embodiment of the present application; it can be seen that the conductivity of the

[100] and

[110] crystal directions shows obvious differences. Fig.10 The curves of the conductivity of cobalt nanointerconnects with different crystal plane structures as a function of voltage show that when the bias voltage is low, the conductivity of the

[110] crystal orientation is significantly higher than that of the

[100] crystal orientation, while this advantage gradually decreases at high bias voltages.

[0109] Fig.11 The IV characteristic curves of cobalt nanointerconnects with different crystal plane structures in the embodiments of the present application show that under the same voltage, the current of the

[110] crystal orientation is significantly higher than that of the

[100] crystal orientation, which indicates that the

[110] crystal orientation has better conductivity, indicating that different crystal planes have different electron transmission efficiencies, and the electrical behaviors of cobalt nanointerconnects with different crystal orientation structures are different.

[0110] Fig.12 Figure 2 is the transmission probability curve of cobalt nanointerconnects with different crystal plane structures. It can be seen that different crystal planes have a significant effect on the transmission probability. The transmission probability of the

[110] crystal orientation in the positive energy region changes greatly, while that of the

[100] crystal orientation is relatively small.

[0111] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing cobalt nanowires, characterized in that: It includes the following steps: S1. Magnetron sputter deposit an Au layer on one side of the double-pass PC membrane; S2. Electro-deposit a Cu layer on the Au layer; The method for electro-depositing the Cu layer is as follows: Inject the Cu electro-deposition solution into one side of the electro-deposition tank, use a Cu rod as the anode, a saturated calomel electrode as the reference electrode, and the Au layer obtained in step S1 as the deposition cathode to electro-deposit the Cu layer; S3. Electro-deposit cobalt nanowires in the pores of the double-pass PC membrane, and the cobalt nanowires are connected to the Au layer; The method for electro-depositing the cobalt nanowires is as follows: Inject the cobalt electro-deposition solution into one side of the electro-deposition tank, adjust the pH value of the cobalt electro-deposition solution to a predetermined range, use a cobalt rod as the anode, a saturated calomel electrode as the reference electrode, and the Au layer obtained in step S1 as the deposition cathode to electro-deposit the cobalt nanowires; The pH value of the cobalt electro-deposition solution is 2 - 5.5; When pH = 2, the texture of the cobalt nanowires is [110]; When 2 < pH < 3.5, the texture of the cobalt nanowires is [100] and [110]; When 3.5 ≤ pH ≤ 5.5, the texture of the cobalt nanowires is [100]; S4. Peel the Au layer from the double-pass PC membrane to separate the cobalt nanowires from the Au layer; S5. Place the double-pass PC membrane after peeling off the Au layer in an organic solvent for dissolution, and then perform centrifugal separation to obtain cobalt nanowires.

2. The method for preparing cobalt nanowires according to claim 1, characterized in that: In step S1, the membrane thickness of the double-pass PC membrane is 6 - 30 μm, and the pore diameter is 10 - 100 nm; The thickness of the Au layer is 250 - 350 nm; The vacuum degree of the magnetron sputtering is 9.0×10 -4 ~1.0×10 -4 Pa, the sputtering power is 30~200 W, and the sputtering time is 5~30 min.

3. The method for preparing cobalt nanowires according to claim 1, characterized in that: In step S2, the Cu electro-deposition solution includes CuSO4 and H2SO4; The deposition voltage for electro-depositing the Cu layer is -1.5 - -0.6 V, the deposition time is 800 - 2000 s, and the reduction charge is 10 - 30 C.

4. The method for preparing cobalt nanowires according to claim 3, characterized in that: The molar ratio of CuSO4 to H2SO4 is 1:(0.1 - 0.2).

5. The method for preparing cobalt nanowires according to claim 4, characterized in that: The thickness of the Cu layer is 10 - 30 μm.

6. The method for preparing cobalt nanowires according to claim 1, characterized in that: In step S3, the cobalt electro-deposition solution includes CoSO4 and H3BO3; the deposition voltage for electro-depositing the cobalt nanowires is -1.6 - -1.0 V, and the deposition time is 1000 - 1500 s.

7. The method for preparing cobalt nanowires according to claim 6, characterized in that: The molar ratio of CoSO4 to H3BO3 is 1:(0.1 - 0.5).

8. The method for preparing cobalt nanowires according to claim 1, characterized in that: In step S5, the organic solvent is dichloromethane, and the dissolution time is 1 - 2 h.

9. A cobalt nanointerconnect, characterized in that: Prepared by the method for preparing cobalt nanowires according to any one of claims 1 - 8, the aspect ratio of the cobalt nanowires is (60 - 3000):1.

Citation Information

Patent Citations

  • Method for preparing elliptical magnetic nanowire with large length-diameter ratio and small size

    CN117512595A

  • Method for the preparation of nanometer scale particle arrays and the particle arrays prepared thereby

    US20020145826A1

Cited By

  • Method for manufacturing 10nm-magnitude cobalt nanowire electric transport device based on template / nanowire composite structure

    CN122136093A